The Antibacterial, Antitumor Activities, and Bioactive Constituents’ Identification of Alectra sessiliflora Bacterial Endophytes - Maela, Mehabo Penistacia; van der Walt, Hendriëtte; Serepa-Dlamini, Mahloro Hope (Frontiers in Microbiology, 2022)
Due to increased antimicrobial resistance against current drugs, new alternatives are sought. Endophytic bacteria associated with medicinal plants are recognized as valuable sources of novel secondary metabolites possessing antimicrobial, anticancer, insecticidal, and antiviral activities. In this study, five bacterial endophytes were isolated and identified from the medicinal plant, Alectra sessiliflora and their antibacterial and antitumor activities were investigated. In addition, the crude extracts of the endophytes were analysed using gas chromatography (GC) coupled to time-of-flight mass spectrometry (TOF-MS). The identified bacterial endophytes belong to three genera viz Lysinibacillus, Peribacillus and Bacillus, with the latter as the dominant genus with three species. Ethyl extracts from the endophytes were used for antimicrobial activity against eleven pathogenic strains through minimum inhibitory concentration (MIC). The anticancer activity against the Hela cervical, Hek 293 kidney and A549 lung carcinoma cells were determined by the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxy-phenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay. Lysinibacillus sp. strain AS_1 exhibited broad antibacterial activity against the pathogenic strains with MIC values ranging from 4-8 mg/mL, while Bacillus sp. strain AS_3 displayed MIC of 0.25 mg/mL. Crude extracts of Lysinibacillus sp. strain AS_1, Peribacillus sp. strain AS_2 and Bacillus sp. strain AS_3 showed growth inhibition of more than 90% against all the cancer cell lines at a concentration of 1000 μg/mL. Untargeted secondary metabolite profiling of the crude extracts revealed the presence of compounds with reported biological activity such as antimicrobial, antioxidant, anti-inflammatory, anticancer and antidiabetic properties. This study reported for the first time, bacterial endophytes associated with A. sessiliflora with antibacterial and anticancer activities.